Design, Synthesis, and Biological Evaluation of Ferulic Acid-Piperazine Derivatives Targeting Pathological Hallmarks of Alzheimer’s Disease - Singh G.; Kumar S.; Panda S.R.; Kumar P.; Rai S.; Verma H.; Singh Y.P.; Kumar S.; Srikrishna S.; Naidu V.G.M.; Modi G. (My University, 2025)
Alzheimer’s disease (AD) is the most prevalent cause of dementia and is characterized by low levels of acetyl and butyrylcholine, increased oxidative stress, inflammation, accumulation of metals, and aggregations of Aβ and tau proteins. Current treatments for AD provide only symptomatic relief without impacting the pathological hallmarks of the disease. In our ongoing efforts to develop naturally inspired novel multitarget molecules for AD, through extensive medicinal chemistry efforts, we have developed 13a, harboring the key functional groups to provide not only symptomatic relief but also targeting oxidative stress, able to chelate iron, inhibiting NLRP3, and Aβ1-42 aggregation in various AD models. 13a exhibited promising anticholinesterase activity against AChE (IC50 = 0.59 ± 0.19 μM) and BChE (IC50 = 5.02 ± 0.14 μM) with excellent antioxidant properties in DPPH assay (IC50 = 5.88 ± 0.21 μM) over ferulic acid (56.49 ± 0.62 μM). The molecular docking and dynamic simulations further corroborated the enzyme inhibition studies and confirmed the stability of these complexes. Importantly, in the PAMPA-BBB assay, 13a turned out to be a promising molecule that can efficiently cross the blood-brain barrier. Notably, 13a also exhibited iron-chelating properties. Furthermore, 13a effectively inhibited self- and metal-induced Aβ1-42 aggregation. It is worth mentioning that 13a demonstrated no symptom of cytotoxicity up to 30 μM concentration in PC-12 cells. Additionally, 13a inhibited the NLRP3 inflammasome and mitigated mitochondrial-induced reactive oxygen species and mitochondrial membrane potential damage triggered by LPS and ATP in HMC-3 cells. 13a could effectively reduce mitochondrial and cellular reactive oxygen species (ROS) in the Drosophila model of AD. Finally, 13a was found to be efficacious in reversing memory impairment in a scopolamine-induced AD mouse model in the in vivo studies. In ex vivo assessments, 13a notably modulates the levels of superoxide, catalase, and malondialdehyde along with AChE and BChE. These findings revealed that 13a holds promise as a potential candidate for further development in AD management. © 2024 American Chemical Society.